Essays on inequality aversion, conditional cooperation, and punishment - Beranek, Benjamin (2017)
Recent developments in behavioral and experimental economics have shown that many people display other-regarding motives, in addition to self-interest. These social preferences – which include inequality aversion, conditional cooperation, and motives for punishment – make sense of a number of phenomena left unexplained by standard economic theory. This thesis is a collection of studies examining social preferences using the tools of experimental economics. Chapter 1 introduces the thesis explaining our goals and methods, as well as previewing our substantive contributions. Chapter 2 reports an experiment designed both to replicate and extend previous studies. We elicit and compare stated and revealed inequality aversion at the individual- level for subjects drawn from three different subject pools. Chapter 3 investigates whether inequality aversion, as modelled by Fehr and Schmidt (1999), explains free riding and conditional cooperation in a public good game. Chapter 4 investigates whether observed variation in the directionality of punishment between two subject pools can be explained by the “Culture of Honor” hypothesis. Chapter 5 concludes.